Cooperation of a Religion Teacher with a Family Assistant for the Benefit of a Child - Zellma, Anna (Studia Warmińskie, 2023)
Problem situations which appear in the contemporary family have an impact on the functioning and development of a child. They breed new challenges concerning a religion teacher’s caring, education and prophylaxis-related activities. They require cooperation with various entities, including a family assistant. These activities are driven by care for the child’s comprehensive development, well-being, and safety. A religion teacher can reinforce a family assistant’s professional and diverse activities. This is done by improving the child’s living conditions and leisure time, reinforcing their self-assessment, modelling positive attitudes, organising help in studying, and motivating them to participate in oratory or socio-therapeutic common room activities. Valuable activities include thematic workshops for children, choir meetings and holiday trips. These activities must include direct contact of a religion teacher with parents of children from problem families. Such families should also receive help with the proper religious education of their children. These actions require religion teachers to be constantly present by accompanying children from dysfunctional families and to have the right personality predispositions and pedagogic skills. They breed new challenges concerning the preliminary and permanent formation, in which the status of practical solutions regarding a religion teacher’s cooperation with the family assistant should be enhanced.